Os desvios ortográficos de alunos do ensino fundamental de uma sala de recursos multifuncionais de Uberaba-MG - SANTOS, Renata Aparecida Batista dos (2020)
The present work is the result of action research carried out with the Professional Master’s Program in Portuguese Language and Literature (Profletras-UFTM) and it aims to investigate the difficulties in the process of acquiring Portuguese language orthography presented by students who attend a multifunctional resource class at the elementary and middle school levels of basic education. It also aims to propose an Activity Guide (entitled “Divertigrafando”) from the results found. We investigated different aspects of Portuguese language orthography, the sound-letter (phoneme-grapheme) relationship, and the influence of orality on writing. Thus, in this research, in addition to briefly reflecting on literacy and initial writing instruction, the importance of fun activities and games as mediators of these processes is also discussed, from authors such as Soares (2013), Bortoni-Ricardo (2013), Kleiman (2012), Cagliari (2007), Mantoan (2003), among others, in order to understand some teaching practices capable of catering to children and teenagers who have some type of special need and/or cognitive deficit. This research is also aimed at the perceptions of the students’ phonological awareness. Choosing to investigate this theme is justified in order to identify what the difficulties are and which strategies could be adopted to better develop orthographic skills. The proposal of working in a multifunctional resource class favors a differentiated work with the use of fun activities and learning games. Therefore, this is an essential investigation as it seeks to contribute to a better development of literacy and initial writing instruction of both typical and atypical subjects, that is, those with special educational needs (SEN). In order to survey the orthographic errors present in students’ writing, we first elaborated and applied a diagnostic test of orthographic errors. After this stage, we selected and classified, adapting from Bortoni-Ricardo (2005) and Sene and Barbosa (2019), the types of orthographic errors. In addition, we also designed and applied a questionnaire to the teachers of the students participating in the research to survey attitudes and pedagogical practices regarding the difficulty in teaching orthography. Based on the results obtained, we designed and applied a set of pedagogical playful activities collect in Guide “Divertigrafando. Finally, we applied a new writing test for comparison with the previous results and thus verified if these instruments are truly effective in orthographic acquisition.